Exploring The Phenomenon and Risks of Female Online Motorcycle Taxi Drivers in Metro Lampung From a Maslahah Perspective - Khusaini, Muhammad; Sufiandi, Idris; Ali, Zezen Zainul (Syakhsiyah Jurnal Hukum Keluarga Islam, 2024)
Technological advances have become one of the alternatives for various companies engaged in transportation. In Indonesia itself there are many in this field, at least 2 online motorcycle taxi transportation companies that have grown rapidly, namely Grab and Gojek. Including in Metro City, we often encounter many online motorcycle taxis, in addition to making it easier for the community to also open up jobs as drivers. This profession is not only cultivated by men but also women. However, each job certainly has its own risks, including in online motorcycle taxis. Therefore, researchers are interested in examining how the phenomenon and risks of female online ojek drivers in Metro Lampung in the perspective of maslahah. This study aims to explain the maslahah study of the phenomenon and risks of female online motorcycle taxi drivers in Metro City. This research is a field research (field reserch) and is descriptive analytic. Using a normative-empirical approach, data collection uses methods; observation, interviews with 3 informants, and documentation. The results showed that more to Maslahah Dhurariyyah, because apart from the risks of course the work of women drivers has a role to help the family, meet economic needs, make independent not dependent on husbands, then female consumers who want to use their services. The risks of women online motorcycle taxi workers are; attempted harassment, illness due to overworking the body in unhealthy conditions, getting fictitious orders and being more careful in getting orders and the risk of accidents can be more careful and vigilant. Women workers are more able to manage time with family, in Islam wives are required to carry out their obligations, not neglecting their obligations to their husbands and children as wives, even though they work to help support the family economy.